Effects of square openings in reinforced concrete deep beams - Noor Rahaman, Yahya (2014)
Reinforced concrete (RC) deep beams are usually used in tall buildings' or offshore structures. The presence of web opening in such beams can often be necessary to accommodate crucial services, for instance ventilating as well as air conditioning ducts. This research was conducted to study the effects of opening in RC deep beams with various sizes of Openings as a test parameter. The shape of choice is square opening. The square openings were placed at the top of shear span near support. A total six deep beams with same dimensions (100 mm x 500 mm)and the total length of 1200 mm were cast. Three control deep beams and the remaining deep beam with openings with size of 150x150 mm, 200x200 mm and 250x250 mm were studied. The beams were tested to failure under 4-point bending. The results obtained from the test including load-deflection behaviour, and crack pattern. The reinforced concrete deep beams with openings develop shear-diagonal cracks at the openings corner, due to the stress concentration at sharp edges.. The crack pattern development varies with opening sizes. The cracking development increased as the size of openings increased. The presence of openings in RC deep beams caused significant reduction in the beam strength. As compared to solid deep beam, the reduction of beam strength falls in the range of 43% - 82%. As for RC deep beams with openings, losses in beam capacity about 43%, 51%, and 82% in beam DBS1, DBS2, and DBS3, respectively were obtained. The size of opening plays a crucial part in this study. The larger the opening size, the more severe crack pattern was observed.